2009
DOI: 10.1055/s-0029-1243306
|View full text |Cite
|
Sign up to set email alerts
|

The Risk for Preterm Labor in Women Receiving 17 Alpha-Hydroxyprogesterone Caproate Prophylaxis for Preterm Birth Prevention

Abstract: We sought to identify maternal or clinical characteristics of women likely to develop preterm labor (PTL) at <34 weeks' gestation while receiving 17 alpha-hydroxyprogesterone caproate (17P) prophylaxis. Current singleton gestations with prior preterm delivery enrolled for outpatient 17P administration at <27 weeks' gestation were identified ( N = 1177). Maternal and clinical characteristics were compared between women hospitalized and diagnosed with PTL at <34 weeks' gestation (PTL group, N = 270) and those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…As mentioned above, the main routes are intra-muscular and suppository, whilst the oral route seems to be non-beneficial (23). However, an important study has revealed that women receiving 17-alpha-hydroxyl-progestrone-caproate prophylaxis before 27 weeks' gestation might have even an increased risk for preterm labor (34). Furthermore, it should be kept in mind that progesterone has no role in the prevention of preterm labor in twin pregnancy (35, 36) weekly injections of 17-alpha-hydroxyl-progestrone-caproate as well as vaginal progesterone suppositories can lead to a significant reduction in the rate of recurrent preterm labor among women who had treated with tocolytics to suppress the acute phase and also there is a considerable reduction in the neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the main routes are intra-muscular and suppository, whilst the oral route seems to be non-beneficial (23). However, an important study has revealed that women receiving 17-alpha-hydroxyl-progestrone-caproate prophylaxis before 27 weeks' gestation might have even an increased risk for preterm labor (34). Furthermore, it should be kept in mind that progesterone has no role in the prevention of preterm labor in twin pregnancy (35, 36) weekly injections of 17-alpha-hydroxyl-progestrone-caproate as well as vaginal progesterone suppositories can lead to a significant reduction in the rate of recurrent preterm labor among women who had treated with tocolytics to suppress the acute phase and also there is a considerable reduction in the neonatal complications.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that although greater rate of neonatal mortality in males than females was reported in some studies (7,13), the current study results were consistent with those of the study conducted in Pakistan (10), the neighboring country of Iran. Although many different factors were implicated based on the geographic region of neonatal death including pneumonia, diarrhea, infection, asphyxia, trauma, sepsis, congenital abnormalities, metabolic disorders, pulmonary hemorrhage, necrotizing enter-colitis, and meningitis (10,13,(47)(48)(49)(50)(51)(52)(53), the main causes of neonatal mortality in Iran were respiratory distress syndrome, congenital anomalies, sepsis, infection, asphyxia, and pulmonary hemorrhage (47).…”
mentioning
confidence: 99%
“…These investigations have provided valuable information regarding how 17P is being prescribed by health care providers, 9 rates of recurrent spontaneous preterm delivery, 10 results of late initiation or early termination of 17P treatment, [11][12][13] and influence of maternal characteristics and pregnancy history on treatment success. [14][15][16][17][18][19][20] The safety of 17P in regards to development of gestational diabetes 21 and its effect on preterm uterine contractions 22 have also been examined.…”
Section: Discussionmentioning
confidence: 99%